Improvement of Depression after Treatment of Dural Arteriovenous Fistula: A Case Report and a Review. (28th November 2012) - Nakagawa, Minoru; Sugiu, Kenji; Tokunaga, Koji; Sakamoto, Chihoko; Fujiwara, Kenjiro
Abstract : Patients with dural arteriovenous fistulas (DAVFs) in the transverse-sigmoid sinus suffer from several symptoms: bruit, headache, visual impairment, and so on. But depression is rare in patients with DAVF. The authors reported a rare case presenting the improvement of depression after the treatment of a dural arteriovenous fistula in the left transverse-sigmoid sinus. A 46-year-old male had suffered from depression and was treated with antidepressants at a local hospital for four years. The patient was temporarily laid off due to his depression. Afterwards, he had Gerstmann's syndrome and came to our hospital. A DAVF in the left transverse-sigmoid sinus was demonstrated on the angiogram. The DAVF was successfully treated with endovascular surgery, coil embolization of the isolated diseased sinus through the mastoid emissary vein which was a draining vein from the fistula. After this treatment, his depression as well as Gerstmann's syndrome was improved and the quantity of the antidepressants decreased. The patient returned to work without any antidepressant two years after the treatment. DAVFs might be one of the causes of depression. It may be necessary to evaluate cerebral vessels in patients suffering from depression by using MRA or 3D-CTA even if there are not any abnormal findings on plain CT scans.